The archpastoral Ministry of Metropolitan Veniamin (Fedchenkov) in Latvia in 1948–1951 years - Nun Evfrosiniia (Sedova G.) (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
In this article there are main stages of the archpastoral Ministry and practice of Metropolitan Veniamin (Fedchenkov) in the Latvian SSR after his return home from the USA in 1948. Metropolitan Veniamin consistently built the relationships with two commissioners of the Council for Russian Orthodox Church Aff airs under the Council People Commissars of the USSR during his administration of the Riga diocese from 1948 to 1951. The authors draw on a wide range of archival sources and show that Metropolitan Veniamin was a law-abiding, but his main concern was the preservation of the internal Church autonomy in the conditions of harsh Soviet pressure and establishment of a constructive interaction with the state. In the article special attention is given to the situation of Latvian parishes, as well as Archpastor’s thoughts about the future of the Orthodox Church in Latvia and his actions for the strengthening of Orthodoxy among Latvians in the period of his administration of the Riga diocese.